Colonoscopy in the Elderly Symptomatic Patients: It is Safe and High Yield - Abd Jaafar, Muhammad; Sainal, Mohd. Yusof; Elagili, Faisal; Aidid, Edre; Md Nor, Azmi (2021)
OBJECTIVE Colonoscopy is the gold standard for investigation of lower GI symptoms. In elderly patients, colonoscopy may have an increased risk of complications. The purpose of this study was to assess the safety and diagnostic yield of colonoscopy in patients aged 65 years and older. METHODS We reviewed retrospectively the endoscopic and pathologic reports for all patients aged 65 years and older who underwent colonoscopy between 2018 and 2020 in our institution. Patient characteristics, indications for examination, findings at colonoscopy, and complications were recorded and analyzed. RESULTS One hundred eight patients (56% male) underwent colonoscopy, mean age 72 ± 5 years. Forty-seven percentage of patients were ASA grade II. There were 35 cases (33 percent) of incomplete examinations. Adenoma detection rate was 40%, cancer detection rate was 11% and total detection rate, including adenoma and cancer was 51%. A total of two significant complications (perforation) were recorded (1.8%). CONCLUSION Although colonoscopy completion rates in symptomatic elderly patients are below recommended rate, it is safe and has a high diagnostic yield.